Petrology, Geochemistry and Geodynamic Significance of the Mafic and Ultramafic Rocks of the Akou (Okondja Basin, Gabon) - Cedric Ligna; Mathieu Moussavou; Karen Bakakas; Michel Mbina; Tomohiko Sato (European Scientific Journal, ESJ, 2018)
The Akou section (Okondja in the Francevillian Basins, Gabon) has a set of mafic and ultrmafic magmatic rocks with various deposit patterns; interbedded basaltic flows, sills and small intrusive bodies within the formations FB francevillian series. The succession of these rocks pyroxenites, gabbros and basalts characterizes the oceanic crust. These rocks mainly consists of olivine, pyroxene, amphibole and biotite. This mineralogical continuation shows that these rocks result from process of split crystallization of an ultramafic magma. The geochemical analyses reveal the major elemental composition such as Na2O (0.24-3.47) and K2O (0.04-3.95). These values indicate that these series are originated from the alkaline magma, which is associated with within plate oceanic volcanicity.